2011
DOI: 10.1007/s11906-011-0243-6
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine and the Metabolic Syndrome

Abstract: Epinephrine is the prototypical stress hormone. Its stimulation of all α and β adrenergic receptors elicits short-term systolic hypertension, hyperglycemia, and other aspects of the metabolic syndrome. Acute epinephrine infusion increases cardiac output and induces insulin resistance, but removal of the adrenal medulla has no consistent effect on blood pressure. Epinephrine is the most effective endogenous agonist at the β2 receptor. Transgenic mice that cannot make epinephrine and mice that lack the β2 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 48 publications
1
46
0
3
Order By: Relevance
“…Improved glucose homeostasis in the GTVE group may be associated with green tea activation of the SNS. With aging, the sensitivity of β 2 -adrenergic receptors declines; as a consequence, exercise may fail to lower blood glucose levels as demonstrated in old obese mice, where β 2 agonists were able to lower blood glucose [41]. It is possible that in our study exercise levels were not enough to lower blood glucose levels because of the age limitations of the participants; however, green tea as an SNS activator along with exercise made a reduction of blood glucose possible.…”
Section: Possible Mechanism Of Reducing Blood Glucose Levels By Gtvementioning
confidence: 78%
“…Improved glucose homeostasis in the GTVE group may be associated with green tea activation of the SNS. With aging, the sensitivity of β 2 -adrenergic receptors declines; as a consequence, exercise may fail to lower blood glucose levels as demonstrated in old obese mice, where β 2 agonists were able to lower blood glucose [41]. It is possible that in our study exercise levels were not enough to lower blood glucose levels because of the age limitations of the participants; however, green tea as an SNS activator along with exercise made a reduction of blood glucose possible.…”
Section: Possible Mechanism Of Reducing Blood Glucose Levels By Gtvementioning
confidence: 78%
“…Indeed, it has been suggested that ChE inhibitors exacerbate this ACh-induced catecholamine release (Akiyama et al, 2003), which could trigger transient hyperglycemia by decreasing insulin-stimulated translocation of glucose transporters to the plasma membrane (Mulder et al, 2005). Ultimately, the excessive release of catecholamines could lead to insulin resistance (Ziegler et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to minimise stress to the experimental animal in all in vivo studies of glucose homeostasis because it is well established that activating the stress response, with the subsequent elevations in adrenaline and noradrenaline, has major physiological effects on glucose handling (Nonogaki 2000, Ziegler et al 2012, which will complicate the interpretation of the experimental data. This is particularly relevant in protocols that involve restraint or repeated handling of the animal, which are acknowledged stressful stimuli (Balcombe et al 2004, Buynitsky & Mostofsky 2009).…”
Section: Stress and Anaesthesiamentioning
confidence: 99%